2018
DOI: 10.1101/238386
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A temporally dynamic Foxp3 autoregulatory transcriptional circuit controls the effector Treg programme

Abstract: Regulatory T cells (Treg) are negative regulators of the immune response.Whilst thymic Treg generation is well studied, it is not known whether and how Collectively, our study dissects time-dependent mechanisms behind Foxp3-driven T cell regulation, and establishes the Foxp3-Tocky system as a tool to investigate the mechanisms behind T cell immunotherapies.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 38 publications
4
36
0
Order By: Relevance
“…Using Nr4a3 –Tocky, we have shown that Foxp3 expression in the thymus occurs in T cells that have received temporally persistent TCR signals . Furthermore, using Foxp3 –Tocky we showed that Foxp3 transcription is initiated in non‐T reg cells during inflammation in the periphery . In humans, activation‐induced Foxp3 in conventional T cells suppresses their proliferation and cytokine production in a cell‐intrinsic manner .…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Using Nr4a3 –Tocky, we have shown that Foxp3 expression in the thymus occurs in T cells that have received temporally persistent TCR signals . Furthermore, using Foxp3 –Tocky we showed that Foxp3 transcription is initiated in non‐T reg cells during inflammation in the periphery . In humans, activation‐induced Foxp3 in conventional T cells suppresses their proliferation and cytokine production in a cell‐intrinsic manner .…”
Section: Introductionmentioning
confidence: 95%
“…As the immunosuppressive T reg population is commonly identified by the expression of Foxp3 (as Foxp3 + T cells in mice and Foxp3 high CD45RA + or Foxp3 + CD127 – CD25 high T cells in humans), the investigation of Foxp3 dynamics in vivo , especially during immune responses, will be key for understanding the in‐vivo dynamics of T reg and T cell regulation. To this end, we have recently developed a new technology, the Timer of cell kinetics and activity (Tocky) system, which allows the investigation of invivo dynamics of Foxp3 and T regs during physiological immune responses .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations